A fast and reliable detection of indigo in historic and prehistoric textile samples. (3rd September 2015) - Kramell, A.; Porbeck, F.; Kluge, R.; Wiesner, A.; Csuk, R.
Abstract : Across all cultures and over all time periods, as early as the third millennium BC, indigo, a very intense blue vat dye, has been used to dye textiles. Even today, indigo is regarded as one of the most popular blue colorants in items such as blue jeans. While synthetic indigo is used to color textiles today, throughout history, a variety of plants have provided indigo. In this special feature article, René Csuk and co‐authors propose to use atmospheric solids analysis probe mass spectrometry (ASAP‐MS) to very rapidly and reliably identify indigo colorants tiny amounts in ancient historic fabrics without any sample preparation. The ionization in ASAP experiments is effected by Penning ionization or by the transfer of protons originating from protonated clusters of water. Dr. René Csuk is Professor of organic bioorganic chemistry at the Martin‐Luther Universität Halle‐Wittenberg (Halle, Germany). His main research interests are in organic and medicinal chemistry, chemical biology and phytochemistry. Graphical Abstract : Historical samples can be investigated conveniently using ASAP®‐MS experiments. ASAP®‐MS allowed for rapid direct sampling without any preparation of the sample prior to its measurements, and reliable results were generated in less than 1 minute. As demonstrated for indigoid‐type dyes, the efficacy of ASAP®‐MS analysis is independent of the type of fiber, the age of the sample, the workmanship, and the state of preservation.